Intra-family relations of the residents of pertubuhan kebajikan warga tua nurul saadah, Terengganu: guiding principles from the qur’anic perspective - Wan Mohd Nasir, Wan Hazwani; Fatah Yasin, Raudlotul Firdaus (Global Business and Social Entrepreneurship ( GBSE ), 2016)
Elderly care centres primarily emphasizes social and personal requirements of senior citizens. The number of elderly being sent to elderly care centres in Malaysia has increased due to the rapid growth of the elderly population. Regrettably, a significant number of problems have been identified among the residents at these centres including children’s refusal to take care of their elderly parents because of their limited abilities, time constraint, financial and health problems as well as responsibility in negligence. These problems are closely related to the intra-family relationship and have been identified as one of the contributing factors in the mistreatment of some elderly residents admitted to these centres.Thus, this study attempts to propose Islamic guiding principles in highlighting the responsibilities of children towards their parents in these centres by focusing on the residents of Persatuan Kebajikan Warga Tua Nurul Saadah, (PKWTNS) as a case study. The study will employ inductive method, observation and interview as the main methods for completing the research.